Estrogen Preserves Pulsatile Pulmonary Arterial Hemodynamics in Pulmonary Arterial Hypertension - Liu, Aiping (Ann Biomed Eng, 2016)
Pulmonary arterial hypertension (PAH) is caused by extensive pulmonary vascular remodeling that increases right ventricular (RV) afterload and leads to RV failure. PAH predominantly affects women; paradoxically, female PAH patients have better outcomes than men. The roles of estrogen in PAH remain controversial, which is referred to as “the estrogen paradox”. Here, we sought to determine the role of estrogen in pulsatile pulmonary arterial hemodynamic changes and its impact on RV functional adaption to PAH. Female mice were ovariectomized and replenished with estrogen or placebo. PAH was induced with SU5416 and chronic hypoxia (SuHx). In vivo hemodynamic measurements showed that (1) estrogen prevented loss of pulmonary vascular compliance with limited effects on the increase of pulmonary vascular resistance in PAH; (2) estrogen attenuated increases in wave reflections in PAH and limited its adverse effects on PA systolic and pulse pressures; and (3) estrogen maintained the total hydraulic power and preserved transpulmonary vascular efficiency in PAH. This study demonstrates that estrogen preserves pulmonary vascular compliance independent of pulmonary vascular resistance, which provides a mechanical mechanism for ability of estrogen to delay disease progression without preventing onset. The estrogenic protection of pulsatile pulmonary hemodynamics underscores the therapeutic potential of estrogen in PAH.